Exploring factors affecting health extension workers motivation in selected urban, rural and pastoralist districts of Ethopia - Shega, Sisay Abebe (My University, 2014)
Introduction: Ethiopia launched a nationwide Health Extension Program (HEP) in 2003 with a view to addressing major health problems of the country by mainly focusing on essential promotion, preventive and selected high impact curative services that target households. The country’s health care service depends on close to 39,000 Health Extension Workers (HEWs). Deployment of HEWs alone was reported to be was not enough to achieve better health outcome. Motivating such a workforce is an important element that deserves attention of all stakeholders. This study explored factors affecting HEWs motivation in rural, urban and pastoralist districts of Ethiopia in 2012. Methods: In this qualitative study, 19 people were interviewed: 12 HEWs and seven key informants from rural, urban and pastoralist districts of Ethiopia. Data on factors motivating and de-motivating HEWs as well as government HEP coordinators’ perceived support to HEWs motivation were gathered and analyzed. Results: Supportive supervision, continuing education, career structure and salary have been identified by rural HEWs as major motivating factors while they found competing interests such as marriage and family issues, absence of housing, and unrealistic performance expectation as factors inhibiting their motivation. The major factors found to be de-motivating for pastoralist HEWs were absence of transportation, poor supervision, insufficient training and lack of capacity among others. Absence of career development and limited recognition were also mentioned as de-motivating for urban HEWs. Conclusion: HEWs play a pivotal role in Ethiopia’s HEP. As such, their motivations require special consideration to support them to continue doing their health care activities in a productive way.